Adaptatives Responses of the Species Ethmalosa fimbriata in Biétri Bay, a Highly Disturbed Environment - Side, Moussa; Alla, Eby Yoboué Gnamma Honorine; Kakou, Behiri Innocent; Adepo-Gourene, Béatrice Abouo (Journal of Biology and Life Science, 2021)
The growth and size at first sexual maturity of the species Ethmalosa fimbriata were studied in two sites in the Ebrié lagoon: Bietri, a highly anthropized environment and Vitré 2, a reference site. Growth parameters estimated from size frequencies showed that growth in both size and weight was faster in females than in males regardless of habitat. On the other hand, specimens from Biétri bay have a slower growth rate than those from Vitré 2. In Bietri bay, individuals are characterized by early sexual maturity. They reach sexual maturity at the age of 0.55 years (about 7 months), corresponding to a size of 6.13 cm for males and 8.42 cm for females; whereas in Vitré 2, they reach sexual maturity at the age of 0.82 years (about 10 months) corresponding to a size of 10.22 cm and 12.94 cm for males and females respectively. These results show that in a highly antropic environment, the growth of Ethmalosa fimbriata is affected and individuals reproduce earlier.